Tio2 Photocatalyzed Degradation of the Azo Dye Disperse Red 1 in Aqueous Micellar Environments† - Pino-Lopez, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Castro-Valenzuela, P; Castro-Valenzuela, P (Blackwell Publishing Inc., 2021)
The photoinduced degradation of the azo dye Disperse Red 1 was studied in a microheterogeneous system comprising titanium oxide (TiO2) and sodium dodecyl sulfate, exposed to UV light. Degussa P25, Anatase and TiO2 synthesized in acidic conditions were supported on raschig rings. The TiO2 photocatalyzed degradation is enhanced in the vicinity of the surfactant critical micelle value. Further increase on the surfactant concentration leads to a loss in photodegradation performance up to values equivalent to that observed without surfactant. Surfactant influence can be explained by two different phenomena taking place. The increasing concentration of surfactant leads to an increase in micellar concentration, inducing the incorporation of the dye to the hydrophobic moiety of the micelles, rendering the hydroxyl radical unable to interact with the dye. Similarly, the increased concentration of micelles at the photocatalyst/water interface might lead to a decrease in the number of active sites on the TiO2 surface able to either generate reactive species and/or interact with de dye molecules. Additives such as H2O2, NaCl, Na2SO4, and Na2CO3 are able to override the influence of the surfactant both positively and negatively, being the final outcome of the influence highly dependent on the crystalline form of the TiO2 photocatalyst. © 2020 American Society for Photobiology